Postanesthetic complications and nursing procedures in after-surgery patients (Horizontes de Enfermería, 2018)
This research is of crucial interest at the local, national and global levels because it treats about the urgent need of improving the nursing procedures in the surgical center area, since the staff who labor in this area must have deep knowledge and specialized technical-scientific skills. In addition, they must develop a wide capacity of critical judgment based on intellectual abilities and scientific theory, which allows not only humanistic application of quality and warmth but above all responsibilities as defenders of the health of our patients. The aim of this research was to know if there could be post-anesthesia complications in post-operative patients of our institution due to the error or omission of a procedure in the immediate post-operative period until the patient is discharged from the surgical area of "‹"‹the Hospital General Luis Gabriel Dávila (HLGD ) in the period March - September 2015, Tulcán Canton, Province of Carchi. 180 patients were treated in the post-operative recovery area, the prevalence of complications in these patients was 32.8% who presented some type of sign or symptom related as a complication. Further, 18 professional of nursing, who work in this area, were evaluated taking into account their work done during the pre and trans-operative to classify patients with a kind of complication. Data that was analyzed in order to draw realistic conclusions according to the problem and proposed hypotheses.
Keywords: Post-anesthesia Complications; Nursing Procedures; Immediate Post-operative; Nursing Behavior